Análise do PROEJA e PROEJA FIC nas pesquisas dos Programas de Pós-Graduação Stricto Sensu em educação na região sudeste do Brasil (2010-2017) - Gregol, Vanessa Patrícia de Fátima (2019)
This dissertation had as a problematic of research to investigate what were the results related to the analysis of implantation and implementation of PROEJA/PROEJA FIC, from 2010 to 2017, in scientific productions of Stricto Sensu Programs of Under-graduation studies in Brazil’s Southeast. The specific objectives were: a) to demonstrate the context of elaboration and the legal bases for the implementation of PROEJA/PROEJA FIC, from 2010 to 2017. The locations of study were Mato Grosso (Cáceres, Cuiabá and São Vicente) (STERING, 2015); Espírito Santo (Vitória) (SILVA, 2016); São Paulo (D’ÁVILA, 2015); Santa Catarina (Florianópolis) (LOSSO-FILHO, 2011) and Amazonas (Manaus, Coari and São Gabriel da Cachoeira) (SANTOS, 2013); and in thecities of Uberlândia – Minas Gerais (MEDEIROS, 2013); Formosa – Goiás (BRITO, 2017), Francisco Morato, Guarulhos, Itapevi, Osasco, São Bernardo do Campo, and Várzea Paulista – São Paulo (BRONZATE, 2014), Serra (Espírito Santo) (BATISTA, 2011); and Alimentation Security Course (MASCHIO, 2011). The implementation of PROEJA FIC, as one of the opportunities to return to school and the insertion in the labor market, answered the needs of professional formation for workers. Between the relevant problems that were highlighted by the researchers, we looked at the scholar evasion, the conflict between municipal, state, and federal governments, the education environment structure, and the difficulties to assist that new demand formed by EJA public.